Reconciling Liberalism and Islamic Educational Values in Indonesia - Kholil, Ibrahim; Assaggaf, Muhammad Yusril Ihza Mahendra; Ramdhani, Deddy (Program Studi Aqidah dan Filsafat Islam, 2025)
The encounter between liberalism and Islamic education creates a complex set of challenges and opportunities, particularly regarding the authority of revelation, the role of scholars, and the spiritual orientation of Islamic pedagogy. This article critically analyzes the historical evolution and foundational principles of liberalism, examining their implications for global education and their specific tensions within the context of Islamic educational frameworks. Drawing on a literature-based methodology with historical and philosophical approaches, the study explores how reformist figures and institutions in Indonesia have developed adaptive, integrative models that selectively incorporate liberal values, such as critical thinking, rational inquiry, and curricular flexibility, while steadfastly preserving core Islamic beliefs and communal identity. The findings reveal that a critically reflective and value-based engagement with liberalism can enrich Islamic education and enhance its relevance, provided it is guided by strong spiritual foundations and ethical discipline. The study offers important implications for curriculum design, educational policy, and future empirical research aimed at sustaining the integrity and adaptability of Islamic education in a globalized world.